2018
DOI: 10.1177/2045125318754472
|View full text |Cite
|
Sign up to set email alerts
|

Switching and augmentation strategies for antipsychotic medications in acute-phase schizophrenia: latest evidence and place in therapy

Abstract: In terms of effectiveness of antipsychotics in schizophrenia, discrepancy often exists between results from double-blind randomized controlled trials and observations in emergency or acute-phase clinical practice. For instance, the antipsychotic switching strategy is not always applicable in emergency or acute-phase situations, and augmentation of another antipsychotic is occasionally done instead. In this review, we discuss strategies for early nonresponse to an antipsychotic drug such as switching and augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…It remains uncertain whether the particular antipsychotic medications involved in a switch are relevant to the response, even though studies have hinted that a switch to amisulpride or quetiapine, or from risperidone to olanzapine (compared with olanzapine to risperidone), may achieve some clinical benefit (Hashimoto et al, 2015; Hatta et al, 2018; Kim et al, 2016). However, the antipsychotic formulation may have an influence; while switching from an oral antipsychotic to a depot/LAI may be beneficial (Schreiner et al, 2017), poorer outcomes have been reported for patients switching from a depot/LAI antipsychotic to oral antipsychotic medication (Barnes et al, 2013; Mustafa, 2017; Voss et al, 2015), which presumably partly reflects the opportunities for covert non-adherence with the latter as well as possibly the pharmacokinetic differences between oral and depot/LAI preparations.…”
Section: Maintaining Responsementioning
confidence: 99%
“…It remains uncertain whether the particular antipsychotic medications involved in a switch are relevant to the response, even though studies have hinted that a switch to amisulpride or quetiapine, or from risperidone to olanzapine (compared with olanzapine to risperidone), may achieve some clinical benefit (Hashimoto et al, 2015; Hatta et al, 2018; Kim et al, 2016). However, the antipsychotic formulation may have an influence; while switching from an oral antipsychotic to a depot/LAI may be beneficial (Schreiner et al, 2017), poorer outcomes have been reported for patients switching from a depot/LAI antipsychotic to oral antipsychotic medication (Barnes et al, 2013; Mustafa, 2017; Voss et al, 2015), which presumably partly reflects the opportunities for covert non-adherence with the latter as well as possibly the pharmacokinetic differences between oral and depot/LAI preparations.…”
Section: Maintaining Responsementioning
confidence: 99%